Effects of Social Support Program on Resilience and Quality of Life of Patients with Cancer in Community, Nakhon Si Thammarat Province - Chuenchoksant, Naruemon; Aekwarangkoon, Saifon; Noonil, Naiyana; Kunset, Pikuntip; Jantasuwan, Rachadaporn (Science, Technology, and Social Sciences Procedia, 2025)
This study aimed to investigate the effects of a social support program on resilience and quality of life among cancer patients in the community. The sample consisted of 84 cancer patients divided into experimental and control groups, with 42 participants in each group. The experimental group received the social support program, while the control group received the usual care. The research instruments consisted of a social support program, a manual, a personal and health status questionnaire, a resilience scale, and a quality-of-life scale. Data were analyzed using frequency, percentage, mean, standard deviation, and ANOVA Repeated Measures. The findings revealed that: 1) In the experimental group, the mean resilience score after the program was significantly higher than before and during the experiment (p < 0.001, F = 49.879). In the control group, the post-experiment score was also significantly higher than during and before the experiment (p < 0.001, F = 7.476). 2) In the experimental group, the mean quality of life score was significantly higher after the program than before and during the experiment (p < .001, F = 25.139). In the control group, the mean quality of life score after the experiment was higher than before but lower than during the experiment, with no statistically significant difference (p > .05, F = 2.853). 3) The comparison of mean scores for resilience and quality of life before, during, and after the experiment between the experimental and control groups showed that the mean resilience score in the experimental group was significantly higher than in the control group both during and after the experiment (p < 0.001). For quality of life, the experimental group had a significantly higher score than the control group during the experiment (p < 0.01). However, when comparing the scores during and after the experiment, the mean scores of both groups were not significantly different (p > 0.05). The findings suggest that the social support program positively impacts resilience and quality of life for cancer patients in the community. Community nurses and relevant stakeholders should continue implementing such programs to support cancer patients.